The type and function of metaphors in Jordanian economic discourse: A critical metaphor analysis approach. (September 2022) - Zibin, Aseel
Abstract: While conceptual metaphors yield various linguistic expressions that reflect conceptual mappings between the source and target domains, there is another type of metaphor which is also constructed cognitively except that these metaphors are "single", in the sense that they are not reflected by several metaphorical expressions. These metaphors do not constitute a conceptual scheme in which many metaphorical expressions enforce the association between the source and target domains. On the basis of Critical Metaphor Analysis Approach, this paper systematically analyses the types and function of metaphor used in a specialised corpus containing 9.5 million words collected from two Jordanian newspapers to describe economic concepts in the Jordanian context. It also explores the interaction between conceptual and single metaphors, on the one hand, and conventional and novel metaphorical expressions, on the other. The results reveal that conceptual metaphors and conventionalised metaphorical expressions in Jordanian economic discourse perform a function that can be distinguished from that of single metaphors and novel metaphorical expressions. I argue that the use of the latter seems to be a matter of 'luxury' rather than 'necessity' where luxury refers to linguistic creativity. Highlights: The function of single metaphors is different from that of conceptual metaphors in Jordanian economic discourse. Single metaphors revolutionize the way the economy is being depicted in Jordan. Conceptual metaphors can yield conventionalised and novel metaphorical expressions while single ones only yield the latter. Conventionalised metaphorical expressions make many economic concepts easier to understand. Novel metaphorical expressions are used for linguistic creativity. CMA enables the identification of new metaphors and reveals why certain metaphors were used and not others.